GAMBARAN PENGETAHUAN IBU TENTANG PERKEMBANGAN BALITA DI POSYANDU SUMBER SEHAT KELURAHAN LAWANG KABUPATEN MALANG - Nahdia Aulia Fahmi; Khafidhiyah Nur Insaniyah (Jurnal Medicare, 2026)
Toddler's development is influenced by various interconnected factors, including biological, psychosocial, and environmental elements. Beyond participation in *Posyandu* (Integrated Health Post) activities, a mother's knowledge is a key determinant in the successful monitoring of toddler development. Insufficient maternal knowledge can delay the recognition of developmental disorders, thereby postponing access to early intervention. Children with developmental delays are at risk of difficulties in language, cognition, motor function, and social-emotional skills. Such conditions can affect school readiness, lower academic achievement, hinder social interaction, and ultimately impact productivity and quality of life in adulthood. This study aimed to assess the knowledge of mothers regarding toddler development at the Sumber Sehat *Posyandu* in Lawang Village, Malang Regency, in 2026. A descriptive research method with a cross-sectional design was employed. The study population consisted of all mothers whose toddlers were registered at the Sumber Sehat *Posyandu* in May 2026. A total sampling technique was used, resulting in a sample size of 23 mothers. Data were collected using a 40-item questionnaire administered via Google Forms. The results showed that among the 23 mothers, 12 (52.1%) possessed adequate knowledge, while 11 (47.9%) possessed good knowledge.